2013
DOI: 10.1073/pnas.1300480110
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen C-proteinase enhancer grasps the stalk of the C-propeptide trimer to boost collagen precursor maturation

Abstract: Tight regulation of collagen fibril deposition in the extracellular matrix is essential for normal tissue homeostasis and repair, defects in which are associated with several degenerative or fibrotic disorders. A key regulatory step in collagen fibril assembly is the C-terminal proteolytic processing of soluble procollagen precursors. This step, carried out mainly by bone morphogenetic protein-1/tolloid-like proteinases, is itself subject to regulation by procollagen C-proteinase enhancer proteins (PCPEs) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 48 publications
(57 reference statements)
3
75
0
Order By: Relevance
“…(C) Diagram of the horseshoe shape of BMP-1 deduced by Berry et al [10]. (D) Interaction of the CUB1CUB2 region of PCPE-1 with the stalk region of the procollagen III C-propeptide trimer (CPIII) [57]. remove the N-terminal extensions of procollagens I-III (N-propeptides; see the review by Colige & Bekhouche in this special issue), BTPs are the main enzymes in charge of the rate-limiting step of fibril formation, that is the removal of the C-terminal propeptides.…”
Section: Functions Of Btps: Shaping Organs and Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…(C) Diagram of the horseshoe shape of BMP-1 deduced by Berry et al [10]. (D) Interaction of the CUB1CUB2 region of PCPE-1 with the stalk region of the procollagen III C-propeptide trimer (CPIII) [57]. remove the N-terminal extensions of procollagens I-III (N-propeptides; see the review by Colige & Bekhouche in this special issue), BTPs are the main enzymes in charge of the rate-limiting step of fibril formation, that is the removal of the C-terminal propeptides.…”
Section: Functions Of Btps: Shaping Organs and Tissuesmentioning
confidence: 99%
“…Initially co-purified with BMP-1 from mouse fibroblasts [55], PCPE-1 is a 55 kDa ubiquitous glycoprotein devoid of catalytic activity but able to enhance C-propeptide removal from procollagens I-III up to 10 fold [55][56][57]. Of the three domains forming PCPE-1 ( Fig.…”
Section: Activatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCPE-1 consists of two N-terminal CUB domains that bind to the procollagen C-propeptide and are responsible for enhancing activity (Kessler and Adar, 1989;Takahara et al, 1994;Hulmes et al, 1997;Ricard-Blum et al, 2002;Vadon-Le Goff et al, 2011;Bourhis et al, 2013) and a C-terminal NTR (netrin-like) domain that binds to heparin and heparan sulfate (Moschcovich et al, 2001;Weiss et al, 2010). This latter interaction induces further enhancement of procollagen processing by BMP-1, an effect referred to as superstimulation (Beckhouche et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the C-proteinase activity of BMP-1 was found to be promoted by some particular proteins, such as fibronectin, Procollagen C-Proteinase Enhancer 1 (PCOLCE1; PCPE1), and Secreted Frizzled-Related Protein 2 (sFRP2) [12][13][14]. It has been shown that PCPE1, a secreted 55-kDa extracellular glycoprotein, drives the enzymatic cleavage of type I procollagen via enhancing BMP1 activity in a substrate-specific manner [15][16][17][18]. PCPE1 has three major protein domains: two CUB domains and a C-terminal netrin-like (NTR) domain [19].…”
mentioning
confidence: 99%